Better Stock Trading : Money and Risk Management. - Guppy, Daryl J., 1954- (John Wiley & Sons, 2011)
An in-depth examination of money management methods for consistent trading successIn Better Stock Trading, Daryl Guppy shows readers how to improve returns by using good money management technique???not by increasing risk in trying to win more trades. Readers will learn how to level the market playing field by using the best money management strategies for their particular account size. From the straightforward two percent rule, to pyramiding methods, and overall portfolio management, Guppy presents a selection of strategies, which will allow any independent trader to capitalize on a rising ma.